Detection and Measurement of Staphylococcal Enterotoxin-Like K (SEl-K) Secretion by Staphylococcus aureus Clinical Isolates - Aguilar, Jorge L. (American Society for Microbiology, 2014)
Staphylococcal enterotoxin-like K (SEl-K) is a potent mitogen that elicits T-cell proliferation and cytokine production at very low concentrations. However, unlike the classical enterotoxins SEB and toxic shock syndrome toxin 1 (TSST-1), the gene for SEl-K is commonly present in more than half of all Staphylococcus aureus clinical isolates and is present in almost all USA300 community-acquired methicillin-resistant S. aureus (CA-MRSA) isolates. Sequencing of the sel-k gene in over 20 clinical isolates and comparative analysis with all 14 published sel-k sequences indicate that there are at least 6 variants of the sel-k gene, including one that is conserved among all examined USA300 strains. Additionally, we have developed a highly sensitive enzyme-linked immunosorbent assay (ELISA) that specifically detects and measures SEl-K protein in culture supernatants and biological fluids. Quantification of in vitro SEl-K secretion by various S. aureus isolates using this novel capture ELISA revealed detectable amounts of SEl-K secretion by all isolates, with the highest secretion levels being exhibited by MRSA strains that coexpress SEB. In vivo secretion was measured in a murine thigh abscess model, where similar levels of SEl-K accumulation were noted regardless of whether the infecting strain exhibited high or low secretion of SEl-K in vitro. We conclude that SEl-K is commonly expressed in the setting of staphylococcal infection, in significant amounts. SEl-K should be further explored as a target for passive immunotherapy against complicated S. aureus infection.